Uji Kuat Tekan dan Daya Serap pada Batako dengan Menggunakan Metode Taguchi - Akhmad Sutoni (Jurnal Sistem dan Manajemen Industri, 2018)
The brick making process has two very critical characteristics / Critical To Quality (CTQ) , namely compressive strength and water absorption. For the quality characteristics of the compressive strength the greater the value, the better (Higher The Better). As for the absorption of water the quality characteristics are getting smaller, the better (Smaller The Better). The quality of the brick used as building material must have good quality that can maintain the strength of existing buildings. The quality in question is the compressive strength and absorbency of water produced must be in accordance with the requirements of SNI (Indonesian National Standard). The WS companies produce concrete blocks which have not good quality. The bricks are brittle. The method used in this study is the Taguchi method. Optimal Level Factor setting is Factor A (duration of stirring), Factor B (Pressure), Factor C (Water), Factor D (Drying) and Factor E (Composition of Sand and Lime). Where the optimal factor setting level factor that is most influential and dominant in compressive strength and water absorption is factor E (composition of sand and lime). For compressive strength factor E (sand and lime composition) level 2, 1: 0.25 and for absorption factor E (composition of sand and lime) level 1, 1: 0.5. and to confirm the results of this experimental design study, a percentage of Quality Loss Function of compressive strength and water absorption was obtained after the optimal level setting had a quality increase of 51.91% and a decrease in the Loss function of 78.5%.